Soil Carbonyl Sulfide (OCS) Fluxes in Terrestrial Ecosystems: An Empirical Model. Issue 9 (16th September 2022) - Whelan, M. E.; Shi, Mingjie; Sun, Wu; Vries, Linda Kooijmans‐de; Seibt, Ulli; Maseyk, Kadmiel
Abstract: Measurements of carbonyl sulfide (OCS) enable independent estimates of regional stomatal conductance provided that non‐stomatal OCS fluxes are well constrained. OCS is taken up through plant leaves, following the same pathway as CO2 ; in contrast to CO2, OCS is irreversibly destroyed in plant leaves and plants do not typically exhibit OCS emissions. Ecosystem uptake of OCS can indicate changes in stomatal opening. Here we present an empirical model to assess the potential impact of soil OCS exchange, the non‐Stomatal OCS exchange Empirical Model (SOCSEM, version 0). We created biome‐specific response curves characterizing soil OCS exchange and restricted the model design to require only knowledge of soil moisture and surface temperature because remote sensing observations are available for these two features. Comparing the model to field‐based chamber observations reveal deviations that can be attributed to missing complexity of the ground surface (having excluded litter and plants without regulated stomata), shortwave radiation, or the soil environment. For agricultural regions with known net emissions, we use remotely‐sensed surface temperature data and demonstrate that data resolution can affect anticipated fluxes. We further investigate the influence of regions with unknown soil OCS responses, for example, Arctic tundra. We compare our model to a process‐based and respiration‐based soil OCS exchange model that has been implemented in a land surface model. Further field study of tropical and arctic ecosystems in conjunction with studies of non‐stomatal surfaces in addition to soil (e.g., bryophytes) will increase confidence in applying OCS as a regional tracer for stomatal conductance. Plain Language Summary: Carbonyl sulfide (OCS) uptake over ecosystems is a good proxy for land carbon uptake via photosynthesis when non‐plant OCS exchange is small or at least knowable. From what we have observed, soil OCS fluxes are typically overwhelmed by plant‐based OCS uptake except in the case of wetland soils or when agricultural fields have become hot and dry. In this paper we constructed a model that estimates where soil OCS "hot spots" occur and how important they are for the global balance of OCS. Although this process is known to be fairly complicated, our model uses only soil moisture and surface temperature because these are the two most impactful parameters that can also be observed from space. We identify several potential causes of model‐observation mismatches. For some regions of the world, like the Arctic tundra, there are no published observations and we hypothesize what the OCS exchange might be based on other ecosystems with similar traits. Overall, we note that soil OCS exchange is still much smaller than other surface sinks despite uncertainties. Key Points: Characterizing non‐stomatal fluxes of carbonyl sulfide (OCS) is necessary to use OCS as a tracer of stomatal conductance We construct an empirical model of soil‐OCS fluxes based on long term field flux observations and lab incubation data The cause of deviations between model output and observations are explored using field observations from in‐tact surfaces